Effects of mineral, organic, and biological fertilization on the establishment of Pochonia chlamydosporia var. catenulata (Kamyschko ex. Barron and Onions) Zare & Gams in a protected crop - Charles, Nelson J.; Arévalo, Jersys; Hernández Duquesne, Ailin; Martín Alonso, Nelson J.; Hidalgo Díaz, Leopoldo (Revista de Protección Vegetal, 2015)
Abstract: The objective of this research work was to evaluate the effect of applying different doses of mineral fertilization, organic fertilization (worm humus) or arbuscular mycorrhizal fungi (Glomus hoi-like) separately or in combination on the establishment of the strain IMI SD 187 of P. chlamydosporia var. catenulata. The experiment was carried out using the tomato (Solanum lycopersicum L.) hybrid HA-3108 in a greenhouse at «Los 3 Picos» farm in Havana, Cuba. Colonization of the soil and roots by the selected strain was assessed in each treatment. The number of P. chlamydosporia colony forming units in soil and roots was directly related to the application of arbuscular micorrhizal fungi and worm humus according to the Principal Component analysis and the biplot graph used. A direct relationship between the mineral fertilization and P. chlamydosporia colonization of roots was found, while it was inverse respect the soil colonization. These results indicated that the nutritional treatments favored P. chlamydosporia (IMI SD 187) growth, with more significant effects when the arbuscular mycorrhizal fungi were used combined with the worm humus. Key words: Arbuscular Mycorrhizal Fungi, inorganic fertilization, nematophagous fungi, worm humus. Efecto de la fertilización mineral, orgánica y biológica sobre el establecimiento de Pochonia chlamydosporia var. catenulata (Kamyschko ex. Barron y Onions) Zare & Gams en cultivos protegidos Resumen: El objetivo del presente trabajo fue evaluar el efecto de diferentes dosis de fertilización mineral, fertilización orgánica con humus de lombriz y hongos micorrízicos arbusculares (Glomus hoi-like), aplicados de manera separada o en combinación, sobre el establecimiento de la cepa IMI SD 187 de Pochonia chlamydosporia var. catenulata. El experimento se realizó en cultivo protegido en la Granja «Los 3 Picos», La Habana, Cuba. Se utilizó tomate (Solanum lycopersicum L.), híbrido HA-3108, y se evaluó la colonización de la cepa seleccionada en el suelo y las raíces para cada tratamiento. El análisis de componentes principales, unido al gráfico de biplot, mostró una relación directa entre la utilización de micorriza y humus con el número de colonias de P. chlamydosporia en el suelo y la raíz. La fertilización mineral tuvo una relación directa con el número de colonias en la raíz e inversa con la colonización de este hongo en el suelo. Estos resultados indicaron que los tratamientos nutricionales probados favorecieron el crecimiento P. chlamydosporia (IMI SD 187) y el efecto combinado de micorriza y humus resultó ser el más significativo. Palabras clave: Hongos Micorrízicos Arbusculares, fertilización inorgánica, Hongos nematófagos, humus de lombriz.